Attractiveness, values and evaluations of non-celebrities in print ads: An exploratory study - S. M. Burgess; R. D. Blackwell (South African Journal of Business Management, 2001)
Noncelebrity endorsers are receiving renewed interest because of rising celebrity endorsement fees and perceptions of risk associated with celebrity endorsements. USA and South African university students rated the attractiveness of a noncelebrity endorser appearing in an alcoholic beverage ad, their desire to associate with her and approve of her behaviour, and their value priorities. The results suggest that value priorities influence noncelebrity endorser evaluations directly and indirectly. More specifically, perceived attractiveness partially mediated the effect of value priorities, confirming Kelman's (1961) contentions. Attractiveness appears to be more useful when consumers assess their desire to associate with a noncelebrity endorser while values appear to be more useful in evaluating a noncelebrity endorser's behaviour.
Keywords: 650